The Two Banquets: Mark’s Vision of Anti-Imperial Economics - Nadella, Raj (Interpretation, 2016)
This article examines Mark’s depiction of the empire, specifically the intrinsic and symbiotic link between the empire and economics within first-century Judea. It highlights Mark’s critique of Roman economic structures, the worldview underlying those structures, and the mechanisms the empire employs to maintain them. The article suggests that the kingdom of God inaugurated by Jesus challenges existing structures as it models alternative paradigms of economic transactions.